Mekanisme Pergeseran Temperatur Transisi Liat-Getas Baja Karbon Rendah Pada Berbagai Tingkat Neutron Fluent = The Ductile-Brittle Transition Temperature Shift Mechanism Of Low Carbon Steel At Various Neutron Fluent - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Low carbon steel is used as nuclear reactor core vessel material. Its superior mechanical and nuclear properties at low neutron flux are the main reason for using it as a nuclear reactor vessel material. At the neutron fluent of 3.10" n/cm2 the ductile-brittle transistion temperature mechanism becomes significant to observe especially throughout the usage in nuclear reactor. In this research are used activation, mechanical testing (impact test) and diffraction metallography (TEM) methods. Low carbon steel was irradiated at the neutron fluent of 9.1015 n/cm2, 1,8.1016 n/cm2, 2,4.1016 n/cm2. In annealing condition naught ductile temperature (NDT) of low carbon steel is 40o F, NDT(1,8.10)=51oF,NDT(1.810)=60oF,NDT(9.10)=71oF